Exploring EFL Learners’ Attitudes Toward English Speaking Activities at Titik Nol, Kampung Inggris Pare - Raihan, Muhammad (English Language Education, Universitas Internasional Batam, 2025)
The study’s purpose, participants, and main findings; however, the implications of the research are not clearly articulated. Although the text briefly states that instructors should understand students’ affective components and identify strategies to address challenges, this statement remains too general. The authors should explicitly explain how the findings can inform instructional practices in English-speaking programs for example, by guiding teachers in designing affective-based interventions, adapting classroom activities to reduce anxiety, enhancing support for low-confidence learners, or creating more student-centered speaking environments. Clarifying these implications will strengthen the abstract by demonstrating the practical relevance of the study and highlighting its contribution to teaching and learning in English Village contexts.